Pembangunan kaedah reka bentuk dan fabrikasi diafram beralun silikon menggunakan teknik punaran anisotropik KOH - Norhayati Soin,; Burhanuddin Yeop Majlis, (2006)
This study is on the development of a new design method of silicon corrugated diaphragm using KOH anisotropic etching technique. Design rules for designing and fabricating corrugated silicon diaphragm structures were developed based on the application of the design rules for corrugated metal diaphragm structures which is later being modified. The KOH etching process has been performed by using etching simulation tool of Intellisuite AnisE in order to realize the corrugated structures on the silicon wafer prior to the fabrication process. The disparity of the etching error percentage, De was found to be too small between the simulated and experimental results which are 0.15%